The past and future of EU law : the classics of EU law revisited on the 50th anniversary of the Rome Treaty - Maduro, Miguel Poiares; Azoulai, Loïc, 1971- (Hart, 2010)
This book revisits, in a new light, some of the classic cases which constitute the foundations of the EU legal order and is timed to celebrate the 50th anniversary of the Rome Treaty establishing a European Economic Community. Its broader purpose, however, is to discuss the future of the EU legal order by examining, from a variety of different perspectives, the most important judgments of the ECJ which established the foundations of the EU legal order. The tone is neither necessarily celebratory nor critical, but relies on the viewpoint of the distinguished line-up of contributors - drawn from.